Percepção dos pais/cuidadores sobre o impacto do tratamento odontológico sob anestesia geral na qualidade de vida relacionada à saúde bucal (QVRSB) de pessoas com deficiência - Marques, Késia Lara dos Santos (2020)
Objective: To evaluate the impact of dental treatment under general anesthesia (GA) on the quality of life related to oral health (HRQoL) of disabled people according to the perception of parents/caregivers. Material and Method: This cross-sectional observational study consisted of a sample of 104 parents/caregivers of disabled people. Socio-demographic/socioeconomic data and parameters of oral clinical examinations were collected. HRQoL was measured using the Parental Caregiver Perceptions Questionnaire (P-CPQ) before and after the treatment. The main independent variables were the experience of dental caries, occlusion and periodontal condition diagnosed according to the criteria of the World Health Organization. Statistical analysis was performed using SPSS software, version 24.0. The Kolmogorov Smirnov, Fisher's Exact and the univariate General Linear Model tests (p <0.05) were applied. Results: Dental treatment under GA was efficient in reducing the impact and improving HRQoL in all domains evaluated (p <0.001), with less reduction in the social well-being dimension. Statistically significant correlation was observed between the total P-CPQ score and the baseline DMFT/dmft (r = 0.26; p = 0.007), however, only the oral symptoms domains (r = 0.42; p <0.001) and functional limitation (r = 0.34; p <0.001) showed a correlation with the experience of caries before the treatment. Regarding to occlusion, there was a significant difference between the Angle classification and functional limitation (p = 0.01), emotional well-being (p = 0.003) and total P-CPQ score (p = 0.003). There was no significant difference associated with overjet, and posterior crossbite, however for the overbite there was a statistical difference in the deltas of the emotional (p = 0.03) and social wellbeing domains (p = 0.003). Regarding to periodontal disease, all scores had a significant reduction after treatment, except for the family impact scale domain (p = 0.10). Conclusion: Dental treatment in GA improved the HRQoL of disabled patients.